A case of severe peripartum cardiomyopathy requiring left ventricular assist device implantation despite the absence of late gadolinium enhancement on cardiovascular magnetic resonance imaging. Issue 1 (January 2020) - Takuwa-Shiomi, Chihiro; Ogiso, Masataka; Isogai, Toshiaki; Kato, Ken; Tanaka, Hiroyuki; Kiriu, Takahiro; Masukawa, Ai; Niinami, Hiroshi; Hagiwara, Nobuhisa
Abstract: Peripartum cardiomyopathy (PPCM) is a rare disorder in which left ventricular (LV) systolic dysfunction and symptoms of heart failure (HF) occur in the peripartum period. The time to potential recovery from severe remodeling of ventricular function is difficult to predict. Although lack of late gadolinium enhancement (LGE) in cardiovascular magnetic resonance (CMR) is reportedly associated with functional recovery of the LV in some cardiomyopathies, the impact of LGE in PPCM remains unclear. We herein report a case of a patient with PPCM who demonstrated rapidly worsened ventricular function, leading to requirement of a paracorporeal left ventricular assist device (LVAD) implantation despite absence of LGE in CMR. A 34-year-old Japanese patient, G2P2A0, expecting her third delivery following a full-term pregnancy, experienced heart failure. Severe LV dysfunction and PPCM were diagnosed. CMR showed no LGE. Although standard HF therapy and bromocriptine were given, her cardiac function failed to recover, and she eventually underwent paracorporeal LVAD implantation as a bridge to heart transplantation due to the impossibility of stopping the administration of inotropic agents. <Learning objective: The prognosis of peripartum cardiomyopathy without late gadolinium enhancement in cardiovascular magnetic resonance is reportedly better than that of cases with late gadolinium enhancement. Our patient, who did not have late gadolinium enhancement, showed rapidly worsening ventricular function, leading to the requirement of paracorporeal left ventricular assist device implantation. Patents with peripartum cardiomyopathy should be monitored vigilantly even if they have no late gadolinium enhancement.>